Comparative Profiling of Volatile Compounds in Popular South Indian Traditional and Modern Rice Varieties by Gas Chromatography–Mass Spectrometry Analysis - Ashokkumar, Kaliyaperumal; Govindaraj, Mahalingam; Vellaikumar, Sampathrajan; Shobhana, V. G.; Karthikeyan, Adhimoolam; Akilan, Manoharan; Sathishkumar, Jeyaraman (Frontiers in Nutrition, 2020)
Rice (Oryza sativa L.) is one of major cereal crops cultivated across the world, particularly in Southeast Asia with 95% of global production. The present study was amied to evaluate the total phenolic content (TPC) and to profile the volatile organic compounds (VOCs) of eight popular traditional and two modern rice varieties cultivated in south India. Thirty-one VOCs were estimated by gas chromatography-mass spectrometry (GC-MS). The identified volatile compounds in the ten rice varieties belong to the chemical classes of fatty acids, terpenes, alkanes, alkenes, alcohols, phenols, esters, amides and others. Interestingly, most of the identified predominant components were not identical, which indicate the latent variation among the rice varieties. Significant variations exists for fatty acids (46.9-76.2%), total terpenes (12.6-30.7%), total phenols (0.9-10.0%), total aliphatic alcohols (0.8-5.9%), total alkanes (0.5-5.1%) and total alkenes (1.0–4.9%) among the rice varieties. Of all the fatty acid compounds, palmitic acid, elaidic acid, linoleic acid, and oleic acid predominantly varied in the range of 11.1-33.7%, 6.1-31.1%, 6.0-28.0% and 0.7-15.1%, respectively. The modern varieties recorded the highest palmitic acid contents (28.7-33.7%) than found in traditional varieties (11.1-20.6%). However, all the traditional varieties had higher linoleic acid (10.0-28.0%) than modern varieties (6.0-8.5%). Traditional varieties had key phenolic compounds, stearic acid, butyric acid and glycidyl oleate which are absent in the modern varieties. The traditional variety of seeraga samba and kichilli samba had the highest azulene and oleic acid, respectively. All these indicate the higher variability for nutrients and aroma in traditional varieties. These varieties can be used as potential parents to improve the largely cultivated high-yielding varieties for the evolving nutritional market. The hierarchical cluster analysis showed three different clusters implying the distinctness of the traditional and modern varieties. This study provided the comprehensive volatile profile of traditional and modern rice as a staple food for energy as well as for aroma with nutrition.